Intra-spinal epidural leakage of bone cement during vertebroplasty of an osteoporotic vertebral fracture: case report and review of literature - Rathod, Tushar N.; Shah, Kunal A.; Shende, Chetan (International Journal of Research in Orthopaedics, 2019)
Vertebral fractures are one of the most common complications of osteoporosis. Prolonged and intractable pain leads to immobilization and significant morbidity. Vertebroplasty is designed primarily to relieve pain, and the procedure is considered when osteoporotic vertebral fracture does not respond to a reasonable period of conservative care. Vertebroplasty has a low complication rate with most common complication being adjacent vertebral body fracture and rare complication due to extra-vertebral cement leakage causing nerve root compression or pulmonary embolism. We report a case of 55 year old lady with osteoporotic D12 wedge compression fracture subjected to vertebroplasty resulting in intraspinal cement leakage noticed intra-operatively. Patient underwent immediate decompression, cement extraction and posterior instrumentation. Postoperative course was uneventful.